Bioprosthetic Heart Valves: Upgrading a 50-Year Old Technology - Li, Kan Yan Chloe (Frontiers in Cardiovascular Medicine, 2019)
Prosthetic heart valves have been commonly used to address the increasing prevalence of valvular heart disease. The ideal prosthetic heart valve substitute should closely mimic the characteristics of a normal native heart valve. Despite the development of various interventions, an exemplary valve replacement does not exist. This review provides an overview of the novel engineering valve designs and explores emergent immunologic insights into age-dependent structural valve degeneration.